2009
DOI: 10.4319/lom.2009.7.382
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals growth stage variability in diatom exudates

Abstract: We studied the patterns of waterborne metabolites released by diatom cultures during different growth phases. A carefully optimized enrichment procedure for metabolites from seawater medium facilitated the generation of large-scale sample sets that could be used for metabolic profiling. Samples from cartridge enrichments were directly submitted to ultraperformance liquid chromatography (UPLC) coupled with time-of-flight mass spectrometry (TOF-MS). Metabolic profiling revealed distinct patterns of metabolite re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 38 publications
0
79
1
1
Order By: Relevance
“…In addition, structures and amount of other compounds released by diatoms have been found to change in accordance with the growth period [34]. Eventually, a complex chemical composition was generated in the water surrounding phytoplankton cells, which spread the information of algal cell nutrient content, resulting food quality, and edibility versus toxiticity to copepods [35].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, structures and amount of other compounds released by diatoms have been found to change in accordance with the growth period [34]. Eventually, a complex chemical composition was generated in the water surrounding phytoplankton cells, which spread the information of algal cell nutrient content, resulting food quality, and edibility versus toxiticity to copepods [35].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present the results of metabolite analyses performed on the northern and southern strains of C. socialis from the same experiment described in Degerlund et al (2012) and relate these data to physiology data. A metabolic fingerprinting approach has already been shown to be able to separate phytoplankton species belonging to different genera (Chauton et al, 2003;Barofsky et al, 2009). Here, we demonstrate that metabolic fingerprinting can also be used to distinguish between closely related taxa, such as the 'forms' or pseudocryptic species of C. socialis.…”
Section: Introductionmentioning
confidence: 79%
“…The results from the phylogenetic analysis did not reveal any clear differences among the northern strains in the LSU rRNA gene (Degerlund et al, 2012). Barofsky et al (2009) reported differences in the exudates (metabolites excreted by the organisms) of the diatoms Skeletonema marinoi and Thalassiosira pseudonana during different growth phases, the stationary, exponential and declining phases of growth all being distinguishable. In our study, however, all strains at 13 C were in exponential growth phase, and yet there were differences in their metabolic fingerprints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. marinoi is known to produce polyunsaturated aldehydes (PUAs) mainly heptadienal, octadienal and octatrienal, which have previously been identified as the potential reasons for the detrimental effects on copepods (Ianora & Miralto 2010 and references therein). In addition, S. marinoi produces a wide variety of metabolites, the production of which changes dynamically during different growth phases (Vidoudez & Pohnert 2008, Barofsky et al 2009). During the study period, we would thus expect changes in the respiratory CR of the groups in relation to the abundance of PUAproducing S. marinoi.…”
Section: Introductionmentioning
confidence: 99%